Sediment Transport and Characteristics in Perak River and Kurau River - Saleh, A; Abustan, I; Remy Rozainy M. A. Z., Mohd; Sabtu, N (International Journal of Engineering and Technology, 2018)
Particle size is the most important parameter to deal in sediment transport processes. This parameter is important to determine the class of sediment transport in river. It is also important for the selection of site for sand mining operation through the determination of the size of sediment, sediment capacity and sediment replenishment rate. Data were obtained through observations made from two rivers namely Sungai Perak and Sungai Kurau in Malaysia. The rivers were categorized as wide river for Sungai Perak and small river for Sungai Kurau. For Sungai Perak, the width of river ranges from 248.18 to 338.53 meter whilst the width of Sungai Kurau ranges from 9 to 11 meter. Data covers flow discharges from 130.988 m3/s to 435.915 m3/s for Sungai Perak and from 2.52 m3/s to 4.723 m3/s for Sungai Kurau. Based on the results, the bed load of two rivers are found to be mostly uniform mixture. The results indicate that these two Malaysian rivers mostly have uniform bed load The bed material for the two rivers are poorly graded mixture and the median size of bed loads mostly ranges from 0.62 to 2.94 mm.Â